Organoprotection and quality of life in elderly hypertensive patients receiving indapamide treatment - M. E. Statsenko; T. G. Shcherbakova; A. O. Osipova (Российский кардиологический журнал)
The authors assessed dynamics of 24-hour blood pressure monitoring (BPM), structural and functional cardiac parameters, heart rate variability (HRV), renal function, carbohydrate, lipid, and purine metabolism, potassium level, as well as cognitive-mnestic function and quality of life (QoL), during 12-week indapamide monotherapy (Indap, PRO MED CS Praha, Czech Republic) in elderly patients with arterial hypertension (AH). The study included 25 patients aged 60-74 years, with Stage I-II AH. All participants underwent 24-hour BPM, echocardiography, renal function and HRV assessment, measurement of biochemical parameters, QoL and cognitive-mnestic functions at baseline and after 12 weeks of therapy. Target office BP level was achieved in 86 % of the patients. According to 24-hour BPM results, systolic BP significantly decreased in 24 hours, in daytime and nighttime, diastolic BP - in nighttime only (at baseline - 68, 9±1, 79 mm Hg, after 12-week treatment - 63, 74±1, 83 mm Hg). Circadian BP profile had normalized. Left ventricular myocardial mass reduced from 224, 31±12, 83 to 209, 11±9, 58 g, by 7 %. Moreover, 24-hour microalbuminuria significantly reduced - from 189+21, 2 to 123±20, 3 mg/d (p<0, 05). Prevalence of compromised renal functional reserve decreased by 4, 8 %. Lndap therapy did not affect autonomous homeostasis. Biochemical parameters of carbohydrate, lipid, and purine metabolism did not change significantly during indapamide treatment. Potassium level decreased slightly: from 4, 61±0, 12 to 4, 17±0, 12 mmol/l. QoL, measured by MOS SF-36 questionnaire, improved from 45, 9±3, 0 to 47, 9±3, 2 points. Lndap treatment was also associated with cognitive-mnestic function improvement by 2 %>. Lndap is a highly effective antihypertensive agent for treating Stage I-II AH elderly patients. Lt also demonstrates organoprotective effects and improves QoL.